Tax aggressiveness determinants - Apriyanti, Hani Werdi; Arifin, Muhamad (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - This study aims to examine the effect of capital intensity, inventory intensity, corporate social responsibility and good corporate governance on tax aggressiveness. Good corporate governance variables used in this study were proxied with independent commissioners and audit commitments.Method - This research focused on manufacturing companies listed on the Indonesia Stock Exchange in the period of 2016-2018. 177 samples were collected using a purposive sampling technique from 59 companies over an observation period of 3 consecutive years. The samples were then analyzed using a multiple linear regression.Result - The results of this study show that capital intensity has a positive and significant effect on tax aggressiveness, inventory intensity has a positive but not significant effect on tax aggressiveness, corporate social responsibility has no positive and significant effect on tax aggressiveness, Independent commissioner has a positive and significant effect on tax aggressiveness, and audit committee has a negative but significant effect on tax aggressiveness.Implication - The results show that the company with high capital intensity tends to be more aggressive on tax. Therefore, the tax authorities must be aware to companies with these characteristics.Originality - The addition of corporate social responsibility and good corporate governance as independent variables are thought to be related to the company’s tax aggressiveness.